Determinants of drug-related crimes - Recasata, Ken A.
Using panel data from the United Nations Office on Drugs and Crime, the study analyzes the determinants of drug-related crimes across various countries and time; given a sample of 81 countries from periods 2005-2006. A panel-data linear regression with juxtaposed fixed-effects and random-effects models are used to account for country-fixed and unobserved effects, respectively, across time and countries; joint endogeneity in independent variables; as well as for measurement errors that may exist in the crime data. The results show that regulatory quality and deterrence have a negative relationship with drug-related crime incidences; and counterintuitively, a positive relationship in corruption controls and carbon emissions. Moreover, causality between drug crimes and violent crimes are not found.